Towards greater regulatory co-operation in the Asia-Pacific for boosting e-commerce trade - Arpita Mukherjee; Ketaki Gaikwad; Aahana Srishti (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2024)
The Asia-Pacific (APAC) region, which accounts for over 50 per cent of the world's population and over 35 per cent of the world's gross domestic product (GDP), is one of the fastest growing regions in the world. The region is growing at higher than the global growth rate and is expected to continue on a high growth trajectory. With high economic growth, the APAC region has become the largest e-commerce market in the world. The e-commerce sector in APAC was valued at US2.9 trillion in 2022 and is projected to reach at value of US6.146 trillion by 2030, accounting for a share of more than half the global retail e-commerce market. Rapid urbanisation, along with rise in incomes and technological developments (such as 4IR technologies), have led to the growth of e-commerce in the region. A policy push towards digitalisation by key countries and the coronavirus (COVID-19) pandemic has further facilitated the growth of e-commerce in this region with consumers and micro, small and medium enterprises (MSMEs) increasingly using e-commerce platforms. Producers and exporters are now using e-commerce platforms to enhance their global reach. In many countries, governments have come up with initiatives to support the use of e-commerce platforms by MSMEs for exports. [...]
hdl:20.500.12870/7431
Keywords: L81; F13; F15; F23; 330; Asia-Pacific; E-commerce; Trade; Policy; MSMEs